2014
DOI: 10.1089/scd.2013.0592
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of E2F2 Inhibits Tumorigenicity, but Preserves Stemness of Human Embryonic Stem Cells

Abstract: Tumorigenicity of human pluripotent stem cells is a major threat limiting their application in cell therapy protocols. It remains unclear, however, whether suppression of tumorigenic potential can be achieved without critically affecting pluripotency. A previous study has identified hyperexpressed genes in cancer stem cells, among which is E2F2, a gene involved in malignant transformation and stem cell self-renewal. Here we tested whether E2F2 knockdown would affect the proliferative capacity and tumorigenicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 41 publications
0
23
0
2
Order By: Relevance
“…For instance, reduced activity of E2F2 in T cells results in evidently accelerated rates of proliferation of cancer cells, but this phenomenon was not observed in E2F1 or E2F3 (Opavsky et al 2007). However, time-course analysis in a recent study (Suzuki et al 2014) reported that cell proliferation of viable tumor cells is significantly reduced in vitro after E2F2 is silenced. Furthermore, Ning Wu et al illustrated that inhibition of E2F2 expression arrests cell division in the G1 phase in gliomas (Wu et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, reduced activity of E2F2 in T cells results in evidently accelerated rates of proliferation of cancer cells, but this phenomenon was not observed in E2F1 or E2F3 (Opavsky et al 2007). However, time-course analysis in a recent study (Suzuki et al 2014) reported that cell proliferation of viable tumor cells is significantly reduced in vitro after E2F2 is silenced. Furthermore, Ning Wu et al illustrated that inhibition of E2F2 expression arrests cell division in the G1 phase in gliomas (Wu et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…According to prediction analysis, we found that E2F2 was a potential target of miR-218 based on the evidence that E2F2 was upregulated in glioma (Suzuki et al 2014), and it could regulate the cell cycle and tumor cell proliferation. We performed dual luciferase reporter assay to prove this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various strategies developed to reduce this risk of teratoma formation include prolonged pre-differentiation of ESCs in vitro , blocking signaling pathways that promote proliferation, induction of apoptosis of proliferative ESCs, sorting cells expressing precursor markers, and deleting undifferentiated ESCs immunologically, genetically, and chemically (718). However, it is difficult to obtain a yield of 100% pure differentiated stem cells for transplantation: the contamination of grafts with undifferentiated cells can give rise to teratoma formation (1921).…”
Section: Introductionmentioning
confidence: 99%
“…As células-tronco pluripotentes induzidas (induced Pluripotent Stem cells -iPS) foram criadas na tentativa de se obterem células com maior potencialidade a partir de células adultas (Takahashi & Yamanaka 2006), evitando assim o problema ético das embrionárias. Porém, a segurança de seu uso para a terapia celular ainda é duvidosa visto que para serem obtidas são utilizados vírus e pró-oncogenes durante a transformação da célula adulta, e apesar de alguns estudos procurarem formas de capacitar o uso dessas células para a terapia (Suzuki et al 2014), elas são em geral usadas como modelos in vitro para estudos de doenças que têm difícil acesso ao tecido de interesse, como as doenças neurológicas (Robinton & Daley 2013).…”
Section: B) Células-tronco E Terapia Celularunclassified